Monetary policy and cross-border interbank market fragmentation: Lessons from the crisis - Tobias Sebastian Blattner; Jonathan M. Swarbrick (European Central Bank (ECB), 2018)
We present a two-country model with an enhanced banking sector featuring risky lending and cross-border interbank market frictions. We find that (i) the strength of the financial accelerator, when applied to banks operating under uncertainty in an interbank market, will critically depend on the economic and financial structure of the economy; (ii) adverse shocks to the real economy can be the source of banking crisis, causing an increase in interbank funding costs, aggravating the initial shock; and (iii) central bank asset purchases and long-term refinancing operations can be effective substitutes for, or supplements to, conventional monetary policy.
Keywords: E44; E52; F32; F36; 330; Interbank market; monetary union; financial frictions; cross-border capital flows; unconventional monetary policy